A combined theory for magnetohydrodynamic equilibria with anisotropic pressure and magnetic shear. (2nd February 2017) - Hodgson, J D B; Neukirch, T
Abstract: We present a new approach to the theory of magnetohydrodynamic equilibria with anisotropic pressure, magnetic shear and translational/rotational invariance. This approach involves combining two existing formalisms in order to eliminate their individual weaknesses. The theoretical aspects of the method are explored in detail along with numerical solutions which make use of the method. Eventually, this method could be applied to model various plasma systems, such as planetary magnetospheres.